Investigation of relationships between biochemical polymorphism and some production charecters on local breeds and cross breeds of sheep in konya central animal research institute - Mehmet Nizamlıoğlu; Vahdettin Altunok; İnci Togan; Firuze Kurtoğlu; Zafer Bulut; Hüseyin Düzgün (Eurasian Journal of Veterinary Sciences)
In the study to determine the genetic structure of local breeds and cross breeds of sheep, three different enzyme loci; carbonic anhydrase (CA1), superoxide dismutase (SOD) and esterase D (EsD) were examined by starch gel electrophoresis. In the present study, the red cell enzymes of 375 local breeds and cross breeds of sheep from Konya Central Animal Research Institute were used. For each of the enzyme systems appropriate buffers and chemical for the activity staining were used in accordance with the information given in the literature. The observed bands of the izoenzymes were analysed. For the enzyme loci Ca1, Sod, Esd neither the individuals of local breeds of sheep nor the individuals of cross breeds of sheep exhibited any variation. They displayed identical bands and they were all homozygotes. This study explained that three enzyme systems exhibited monomorphic. It seem that, with respect to the loci studied, cross breeds of sheep do not differ from the local breeds of sheep.